The PHP workshop : a new, interactive approach to learning PHP - Busuioc, Alexandru (Packt Publishing, 2019)
Cut through the noise and get real results with a step-by-step approach to learning PHP programming Key Features Ideal for the PHP beginner who is getting started for the first time Complete step-by-step exercises and open-ended activities to help build and reinforce key skills Structured to let you progress at your own pace, on your own terms Use your physical copy to redeem free access to the online interactive edition Book Description You already know you want to learn PHP 7, and a smarter way to learn PHP development is to learn by doing. The PHP Workshop focuses on building up your practical skills so that you can develop cutting-edge, high-performance web applications. It's ideal if you're looking to work with an existing application, or even develop your own side project with a PHP framework like Laravel. You'll learn from real examples that lead to real results. Throughout The PHP Workshop, you'll take an engaging step-by-step approach to understanding PHP development. You won't have to sit through any unnecessary theory. If you're short on time you can jump into a single exercise each day or spend an entire weekend learning about third-party libraries. It's your choice. Learning on your terms, you'll build up and reinforce key skills in a way that feels rewarding. Every physical copy of The PHP Workshop unlocks access to the interactive edition. With videos detailing all exercises and activities, you'll always have a guided solution. You can also benchmark yourself against assessments, track progress, and receive content updates. It's a premium learning experience that's included with your printed copy. To redeem, follow the instructions located at the start of your PHP guide. Fast-paced and direct, The PHP Workshop is the ideal companion for PHP beginners. You'll build and iterate on your code like a software developer, learning along the way. This process means that you'll find that your new skills stick, embedded as best practice. A solid foundation for the years ahead. What you will learn Get to grips with fundamental concepts and conventions of PHP 7 Work with PHP MySQL databases and build dynamic applications Learn how to compile logical errors and handle exceptions in your programs Explore how PHP unit testing can help create a bug-free development process Integrate third-party packages into your applications Connect external web services to your applications with tools like Guzzle Who this book is for Workshops are ideal for f ...